2008
DOI: 10.1007/s10826-008-9220-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parent–Child Relations and Adolescent Self-Esteem

Abstract: We used data drawn from the National Longitudinal Study of Adolescent Health to assess the independent and interactive correlations of maternal and paternal parenting with adolescent self-esteem. Specifically, ordinary least squares regression was used to provide estimates for a large, culturally diverse sample of married, biological parent-families with adolescent children. Our results suggested that adolescent reports of mothers' and fathers' physical availability, involvement, and quality of relations are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 36 publications
9
62
0
7
Order By: Relevance
“…Although we could not integrate both into one model due to the high intercorrelations, the study supports the expectation that both mothers and fathers are important for early adolescents' self-esteem. This is in accordance with other studies on the relationship between mothers' and fathers' parenting and self-esteem (Bulanda and Majumdar 2009;Milevsky et al 2007;Plunkett et al 2007). However, the result that only fathers' parenting is associated with scholastic competence but not mothers' parenting is surprising.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although we could not integrate both into one model due to the high intercorrelations, the study supports the expectation that both mothers and fathers are important for early adolescents' self-esteem. This is in accordance with other studies on the relationship between mothers' and fathers' parenting and self-esteem (Bulanda and Majumdar 2009;Milevsky et al 2007;Plunkett et al 2007). However, the result that only fathers' parenting is associated with scholastic competence but not mothers' parenting is surprising.…”
Section: Discussionsupporting
confidence: 93%
“…This longitudinal study, using adolescents' self-reports, indicated that parenting quality (parental warmth and psychological control) did indeed mediate the link between adolescents' awareness of marital conflict and subsequent decreases in self-esteem. Further studies also indicate positive relationships between parenting quality and adolescents' self-esteem (e.g., Bulanda and Majumdar 2009;Lamborn et al 1991) and scholastic competence (Bronstein et al 2005;Kokkinos and Hatzinikolaou 2011), lending support to the relevancy of the spillover hypothesis in explaining the negative effect of marital conflict on children's self-evaluation.…”
Section: Parenting Qualitymentioning
confidence: 82%
See 1 more Smart Citation
“…Ancak, bu araştırmanın sonuçları ile Germaine (2001) ve Scott'ın (2004) yürüttüğü araştırma sonuçlarının tutarlılık gösterdiği söylenebilir. Özsaygı, sosyal hayat, ailevi tutumlar gibi pek çok farklı dışsal faktörden etkilenmektedir (Bulanda ve Majumdar, 2009;Frank, Plunkett ve Otten, 2010). Bu araştırma için de böyle bir durumun söz konusu olabileceği, söylenebilir.…”
Section: şEkil 3 Be Puan Ortalamaları Grafiğiunclassified
“…There is a significant role of parents in this process. Supportive behaviors of parent's leads adolescents to feel loved and valued as a person, in other words, affect the adolescent selfesteem in a positive way (32,33). On the other hand, parent-adolescent conflict perceived as unsupportive parenting behaviors by adolescent, and this negatively affects the self-esteem of adolescents (34).…”
Section: Introductionmentioning
confidence: 99%